Coexistence of gastrointestinal stromal tumor (GIST) and colorectal adenocarcinoma: A case report - Evangelos Felekouras; Sotirios Georgopoulos; Frangisca Sigala; Alexandros Papalambros; Papaconstantinou Ioannis; Athanasios Petrou; Efstathios Papalambros; Athanasios Giannopoulos (World Journal of Surgical Oncology, 2007)
Abstract Background Gastrointestinal stromal tumors (GIST) represent the most common mesenchymal tumors of the digestive tract. Over the last ten years the management of GISTs has dramatically altered but their coexistence with other gasrointesinal tumors of different histogenesis presents a special interest. The coexistence of GISTs with other primaries is usually discovered incidentally during GI surgery for carcinomas. Case presentation We present here, a case of a 66-year-old patient with intestinal GIST and a synchronous colorectal adenocarcinoma discovered incidentally during surgical treatment of the recurrent GIST. Immunohistochemical examination revealed the concurrence of histologically proved GIST (strongly positive staining for c-kit, vimentin, SMA, and focal positive in S-100, while CD-34 was negative) and Dukes Stage C, (T3, N3, M0 according the TNM staging classification of colorectal cancer). Conclusion The coexistence of GIST with either synchronous or metachronous colorectal cancer represents a phenomenon with increasing number of relative reports in the literature the last 5 years. In any case of GIST the surgeon should be alert to recognize a possible coexistent tumor with different histological origin and to perform a thorough preoperative and intraoperative control. The correct diagnosis before and at the time of the surgical procedure is the cornerstone that secures the patients' best prognosis.